2021
DOI: 10.1038/s41467-021-26987-1
|View full text |Cite
|
Sign up to set email alerts
|

The APPL1-Rab5 axis restricts NLRP3 inflammasome activation through early endosomal-dependent mitophagy in macrophages

Abstract: Although mitophagy is known to restrict NLRP3 inflammasome activation, the underlying regulatory mechanism remains poorly characterized. Here we describe a type of early endosome-dependent mitophagy that limits NLRP3 inflammasome activation. Deletion of the endosomal adaptor protein APPL1 impairs mitophagy, leading to accumulation of damaged mitochondria producing reactive oxygen species (ROS) and oxidized cytosolic mitochondrial DNA, which in turn trigger NLRP3 inflammasome overactivation in macrophages. NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…Specifically, APPL1 deficiency decreases the expression of the downstream molecule MYOF in osteoporotic hMSCs to cause lysosomal dysfunction and damage, inhibit autophagy flux, and finally promote hMSC differentiation into adipocytes, resulting in bone marrow adipose tissue hyperplasia and a reduced bone mass. Consistent with the findings from our study, Wu et al [ 53 ] revealed autophagosome accumulation in the absence of APPL1 in mitophagy. Although their research object was macrophages, the results revealed a correlation between APPL1 and the autophagic degradation system.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, APPL1 deficiency decreases the expression of the downstream molecule MYOF in osteoporotic hMSCs to cause lysosomal dysfunction and damage, inhibit autophagy flux, and finally promote hMSC differentiation into adipocytes, resulting in bone marrow adipose tissue hyperplasia and a reduced bone mass. Consistent with the findings from our study, Wu et al [ 53 ] revealed autophagosome accumulation in the absence of APPL1 in mitophagy. Although their research object was macrophages, the results revealed a correlation between APPL1 and the autophagic degradation system.…”
Section: Discussionsupporting
confidence: 93%
“…ASCs in a SIRT3-Dependent Manner. Since dysfunctional or damaged mitochondria are removed by a mechanism called mitophagy to maintain cellular homeostasis, we used LC3 immunofluorescence, MitoTracker Red and DAPI triple staining [30] to detect the effect of irisin and AGEs on mitophagy in ASCs. As shown in Figure 6(a), normal levels of mitophagy could be indicated by colocalization of LC3 and MitoTracker Red.…”
Section: Irisin Mitigates Age-induced Abnormal Mitophagy Inmentioning
confidence: 99%
“…First, we detected the impact of Drp1 knockdown on the expression of the mitochondrial marker proteins Tom20 and Cyto C in BMDMs treated with MSU crystals. They are commonly used as mitochondrial markers to reflect damage mitochondrial clearance and mitophagic rate [ 29 ]. Silence of Drp1 alleviated the elevation of Tom20 and Cyto C protein levels induced by MSU crystals ( Figure 6(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…Mitophagy can mitigate the activation of the NLRP3 inflammasome by regulating mitochondrial quality, maintaining mitochondrial homeostasis and eliminating damaged mitochondria [51][52][53]. Defective mitophagy accelerates the activation of the NLRP3 inflammasome, which may lead to metabolic and autoinflammatory diseases [29,54]. Mito/ autophagy is also involved in MSU crystal-induced NLRP3 inflammasome activation or IL-1β release [54].…”
Section: Discussionmentioning
confidence: 99%